Alloy Design of MARBN for Boiler and Turbine Applications at 650 oC. (3rd September 2021) - Abe, Fujio; Tabuchi, Masaaki; Tsukamoto, Susumu
ABSTRACT: Soluble boron stabilises fine distributions of M23 C6 carbides near grain boundaries (GBs) in 9Cr steel during creep, enhancing GB precipitation hardening, and suppresses the Type IV fracture in welded joints at 650 o C. Excess addition of boron and nitrogen produces BN inclusions at high temperature, degrading creep strength and rupture ductility. A 9Cr-3W-3Co-0.2V-0.05Nb steel with 130 ppm boron and 80 ppm nitrogen, designated martensitic 9Cr steel strengthened by boron and nitrides (MARBN), exhibits not only the much higher creep rupture strength of base metal than Gr.92 but also no Type IV fracture in welded joints at 650 o C. The boron and nitrogen concentrations in MARBN are located just inside the phase boundary for BN at normalising heat treatment temperature in the phase diagram, where we can obtain enough soluble boron and soluble nitrogen but no BN inclusion. The oxidation resistance is improved by the pre-oxidation treatment in argon gas.